Congenital Infantile Fibrosarcoma in the Premature Infant. (December 2017) - Edwards, Taryn M.; Duran, Melissa S.; Meeker, Tamara M.
Abstract : Background: Congenital infantile fibrosarcoma (CIF) is rare and represents less than 1% of all childhood cancers. It is a tumor that originates in the connective fibrous tissue found at the ends of long bones and then spreads to other surrounding soft tissues. These lesions are typically large, grow rapidly, and can often be mistaken for teratomas. Diagnosis is confirmed by pathology, where cellular proliferation of fibroblasts occurs. Imaging is an important part of the diagnosis, which includes the use of magnetic resonance imaging and/or computed tomography scan. Although surgical resection is the primary treatment, chemotherapeutic agents may be used as adjuvant therapy. Purpose: To describe modalities for accurate diagnosis and treatment of CIF. Methods/Search Strategy: PubMed was searched using terms "congenital infantile fibrosarcoma" and "infantile fibrosarcoma." Eleven relevant, English language articles were identified and utilized in the preparation of this case presentation. Findings/Results: Complications addressed in this case presentation are prenatal diagnostic challenges, pharmacologic interventions in the setting of prematurity, immunosuppression, and acute liver and renal failure. Pharmacologic treatments will include chemotherapy agents, antimicrobial agents, as well as granulocyte colony-stimulating factor for immunosuppression. Nursing challenges included positioning and integumentary disturbances. Implications for Practice: Utilization of diagnostic imaging and pathology to accurately identify and diagnose CIF is essential. Implications for Research: Safety and efficacy of chemotherapeutic agents in premature infants with CIF need to be established.